The decline of the traditional pension a comparative study of threats to retirement security - Mackenzie, G. A. (George A.) 1950-; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2010)
"The traditional (final or average salary) pension that employers have provided their employees has suffered a huge decline in labor force coverage in the United Kingdom and the United States, and less severe declines in Canada and elsewhere. The traditional pension provides a precious measure of retirement security by paying retirees an annuity for life. This study compares developments in the countries just named and in Australia, Denmark, Germany, Japan, Netherlands, Sweden, and Switzerland to explain the forces behind the decline of the traditional pension and to contrast the experience of public sector employer-provided plans, where it remains dominant. Given the great value of the longevity insurance that the traditional plan provides, and the risks its diminished coverage entails, the book proposes a set of measures that either stem the decline or endow defined contribution pensions with some of the attributes of the traditional plan" -- Provided by publisher
Introduction; Part I: 1. The development of employer-provided pensions; 2. The economics of occupational/employer-provided pension plans; 3. Issues in funding and investing; 4. Regulatory issues; 5. Public sector employer-provided pensions and recent innovations in the first tier; Part II: 6. The causes of decline; 7. Policies to address the decline of the traditional pension; 8. Summary and conclusions; Appendix 1. Ten country profiles; Appendix 2. Mathematical treatments and derivations
Title from title screen (viewed on November 10, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Pensions; Investments; Portfolio management